The effect of soy isoflavones on non-alcoholic fatty liver disease and the level of fibroblast growth factor-21 and fetuin A - Asal Neshatbini Tehrani; Behzad Hatami; Bizhan Helli; Zahra Yari; Ghazal Daftari; Amin Salehpour; Mehdi Hedayati; Elmira Khalili; Seyed Ahmad Hosseini; Azita Hekmatdoost (Scientific Reports, 2024)
Abstract A two-arm randomized open labeled controlled clinical trial was conducted on 50 patients with non-alcoholic fatty liver disease (NAFLD). Subjects were randomized to either receive two tablets of soy isoflavone (100 mg/day) or placebo. At week 12, the serum levels of alanine amino transferase (ALT), aspartate amino transferase (AST) and controlled attenuation parameter (CAP) score were significantly decreased only in the soy isoflavone group (P < 0.05). A significant decline in the gamma glutamyl transferase (GGT) level was observed only in the placebo group (P = 0.017). A significant increase in the serum level of fetuin A was shown in both groups at the end of the trial with a significantly greater increment in the soy isoflavone group compared to the placebo group (P < 0.05). The changes in the serum level of FGF-21 were not significant in any of the two groups. Steatosis grade significantly improved only in the soy isoflavone group (P = 0.045). There was no significant change in the fibrosis grade in the groups. Soy isoflavone intake led to a decrease in ALT, AST, CAP score, steatosis grade and an increase in the level of fetuin A. However, no significant changes were observed in the fibrosis grade and serum levels of GGT and FGF-21.